Antidiarrheal Effect of Lime Peel Extract on Bisacodyl-Induced Mice - Abraham Talent Bawadi Sibarani; Hesti Triwahyu Hutami; Nani Maharani; Yora Nindita (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Diarrhea is a condition of increased fecal water content of more than 200 grams or 200 ml/24 hours with a liquid or semi-liquid consistency. Complications of diarrhea, dehydration and malnutrition are still world health problems. Lime peel extract contains tannins which have astringent properties. Tannins are indicated as an alternative anti-diarrheal agent by tightening and forming a protective layer on the intestinal mucosa thereby reducing osmolarity.Aim: To examine the consistency, fecal water content, and frequency of defecation of bisacodyl-induced diarrhea in mice that are given lime peel extract.Methods: This research was an experimental with post test only group design. Thirty-six male mice were included and then divided into 5 groups with bisacodyl induction and 1 normal control group (KM) without bisacodyl induction. The negative control group (KN) was given 0.5 ml Tween 80 1%, the positive control group (KP) was given attalpugite 0.4 mg/40gW, treatment group 1 (X1), treatment group 2 (X2), treatment group 3 (X3 ) were given lime peel extract at graded doses of 125, 250, and 500 mg/KgW. Consistency, fecal water content, and frequency of defecation were observed every 30 minutes for 4 hours by observing the consistency of feces, weighing wet and dry feces to measure the water content, and measuring the frequency of defecation in each group. Data were analyzed statitiscally using Kruskal Wallis test with Post Hoc Mann Whitney test.Results: There were significant differences between the comparison of defecation frequency in the X3 group and the KM group, for the fecal water content comparison between the X3 group and the KN group, and no significant differences in the following group comparisons.Conclusion: Lime peel extract cannot reduce the frequency of defecation, fecal water content, and increase the consistency of feces significantly.Keywords: Diarrhea, lime peel extract, tannins, astringent, consistency, fecal water content, frequency of defecation.